The relationship between compulsory citizenship behavior and nurses’ silence: a cross-sectional study - Li, Zifeng; Yang, Luhuan; Xi, Zuyang; Yi, Wen; Fu, Yuanzhi; Chang, Caiyun; Lei, Yunhong (BioMed Central, 2025)
Aim: This study aimed to assess the relationship between compulsory citizenship behavior and nurses’ silence. Methods: A descriptive cross-sectional online study was conducted in October 2023, targeting 402 nurses working in Yichang Central People’s Hospital, Hubei Province, China. Data were collected through a structured questionnaire comprising demographic details, the Compulsory Citizenship Behavior Scale, and the Nurses’ Silence Scale. Statistical analyses were conducted using SPSS 25.0, including descriptive statistics, t-tests, one-way ANOVA, Pearson correlation, and hierarchical regression analyses. Results: The study revealed that the overall mean score for nurses’ compulsory citizenship behavior was 14.63 (3.99), while the overall mean score for nurses’ silence was 32.78 (8.28). Significant differences in compulsory citizenship behavior scores were observed among nurses with varying levels of work experience (P < 0.05). Similarly, significant variations in silence scores were identified according to work experience and employment type (P < 0.05). After adjusting for work experience and employment type, a significant correlation was identified between compulsory citizenship behavior and nurses’ silence (P < 0.05). Conclusions: Nurses exhibited moderate levels of compulsory citizenship behavior and silence. Additionally, a significant positive correlation was revealed between compulsory citizenship behavior and nurses’ silence. Recommendation: Nursing administrators should implement targeted measures to lower compulsory citizenship behavior, thereby fostering a more open and communicative environment within the organization, and encouraging nurses to express their opinions more freely.